PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 005 RAJA BEJAMU KECAMATAN SINABOI - Nainggolan, Lowide; Noviana, Eddy; ', Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research aim to to increase process the study and result of learning IPA of class of III SD Country 005 King of Bejamu of Subdistrict of Sinaboi of teaching year 2015 / 2016. this Subjek Research is student of class of II SD Country 005 King Bejamu with the amount of men student as much 10 people and 10 people of woman student. This research represent the Research of Class Action ( PTK) with two cycle executed at even semester of April month;moon 2016. Research data indicate that the study process and result of learning to experience of the make-up of. This matter is provable at activity score learn and student of during study process experience of the make-up of. first Cycle I meeting of activity percentage learn is 62,50% with the good category and mount equal to 4,17% at second meeting become 66,67% with the good category. Hereinafter first cycle II meeting of percentage of teacher activity mount to become 83,33% with the good category very and at second meeting mount equal to 8,34% so that become 91,67% with the category very goodness. Student activity of during study process also mount at first cycle I meeting of percentage of student activity is 58,32%dengan category enough and second meeting mount equal to 0,34% so that become 66,67% with the good category. first Cycle II meeting return to mount to become 75% with the good category, second meeting of percentage of student activity mount equal to 0,33% becoming 83,33% with the category very goodness. Result learn the student also experience of the make-up of elementary score to UH I experience of the make-up of result learn equal to 12% with the complete student amount as much 13 people and which is not complete 7 people. Complete of klasikal UH I is 65% with the average value 71,5 above KKM. UH II also experience of the make-up of result learn from elementary score equal to 12% with the complete student amount 18 people and is not complete 2 people, complete of klasikal UH II 90% with the average value 80,50. From inferential above solution that through/ passing implementation model the study of co-operative of type STAD can improve the process of study IPA in class of III SD Country 005 King of Bejamu of Subdistrict Sinaboi.Keyword : Study Of Cooperative of Type STAD, Process Study